TINJAUAN TENTANG KOLESTEROL DARAH PADA SOPIR BUS PARIWISATA DI KABUPATEN BADUNG - nyoman mastra (Jurusan Analisis Kesehatan, Poltekkes Kemenkes Denpasar, 2017)
ABSTRACT Background The lifestyle of consuming high fatty foods, smoking and drinking coffee frequently in the work place could be expected to cause high cholesterol that affects the health of the tourism bus driver. Objective The aims study to determine a cholesterol levels in tourism bus driver at Badung regency. Methods This research is a descriptive study. Tourism bus driver who works at Indah Putra Transport. Result Of the 39 respondents obtained 18% had normal cholesterol levels and 82% had high cholesterol levels. Based on the frequency of smoking every day, the highest frequency indicated by smoking more than 20 cigarettes per day by 25 respondents (64%). The frequency of coffee consumption < 5 cups per day, 41% had high cholesterol levels, consume coffee > 5 cups of coffee per day, 41% have cholesterol levels high. Based on Physical activity habits 3˗4 times a week indicated 5% had high cholesterol levels and physical activity < 3 times a week indicated 77% had high cholesterol levels. 1˗5 year working period earned as much as 8% had high cholesterol levels, 6˗10 year working period earned 3% had normal cholesterol levels and 23% had high cholesterol and the rest of the respondents were 51% in working period above of 11 years have high cholesterol levels. Conclution It can be conceded that bad lifestyle of tourism bus drivers can affect the level of cholesterol. Keywords : driver, cholesterol, lifestyle